Comportamento ingestivo e consumo de forragem por novilhas de corte em sistemas forrageiros de ciclo estival - Oliveira Neto, Renato Alves de (2011)
ABSTRACT There were evaluated forage intake, ingestive behavior, productive, structural and chemical characteristics of pasture and performance of beef heifers in coastcross (Cynodon dactylon (L.) Pers) and alexandergrass(Urochloa plantaginea Link.) receiving protein supplement or not. The grazing method utilized was continuous with variable number of animals. The experimental design was completely randomized in a factorial 3 x 2, three pasture systems and two phenological stages, called Vegetative and Flowering . There were evaluated the activities of grazing, ruminating and resting, travel patterns and use of feeding stations, ingestive behavior such as mass and bite rate, productive, chemical and structural characteristics of pastures. The forage intake was estimated using a technique with chromic oxide as an indicator of fecal output. The heifers modify the use of feeding stations and travel patterns between phenological stages and between pasture systems. The animals consume more forage in the Vegetative stage (2,81% of BW DM) than the Flowering stage (1,92% of BW DM). Average daily gain, body condition and stocking rate are similar for heifers in coastcross, alexandergrass or in alexandergrass receiving protein supplement. Beef heifers receiving protein supplement in alexandergrass pasture consume more forage than heifers in coastcross, without difference than that exclusively in alexandergrass. Pasture systems with alexandergrass or coastcross provide adequate nutrient intake for heifers to be mated at 18 months old.